2018
DOI: 10.1007/s11605-018-3797-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Predictors for Intestinal and Pancreatobiliary Types of Adenocarcinoma of The Ampulla of Vater

Abstract: CDX2 and CK7 were the immunohistochemical markers that best discriminated the intestinal from the pancreatobiliary type. Lymph node involvement had a high impact on survival and proved to be more frequent in the pancreatobiliary type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Among the periampular carcinomas, the ductal adenocarcinoma of the head of the pancreas (ADCP) has the worst prognosis. The survival of patients undergoing surgical interventions approximates that observed in patients with neoplasia of the papilla or distal choledochus, and belong to the pancreatobiliary subtype 10,11 .…”
Section: Fatores Prognósticos Pré-operatórios Em Pacientes Com Adenoc...mentioning
confidence: 82%
“…Among the periampular carcinomas, the ductal adenocarcinoma of the head of the pancreas (ADCP) has the worst prognosis. The survival of patients undergoing surgical interventions approximates that observed in patients with neoplasia of the papilla or distal choledochus, and belong to the pancreatobiliary subtype 10,11 .…”
Section: Fatores Prognósticos Pré-operatórios Em Pacientes Com Adenoc...mentioning
confidence: 82%
“…On the other hand, CK7 is more often expressed by the pancreatobiliary subtype [ 17 ]. A recent study in 30 patients, identified CK7 and CDX2 as the 2 most discriminating immunohistochemical markers for the distinction between pancreatobiliary subtype and intestinal subtype [ 18 ]. Mucins are high-molecular-weight glycoproteins expressed by epithelial tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The ductal adenocarcinoma of the head of the pancreas (DAHP) presents itself to be the most aggressive tumor of his class with worse clinical prognosis. The Ductal adenocarcinoma of the head of the pancreas shows the extremely aggressive disease, with the worst prognostic factors being old age, presence of comorbidities, previous history of cancer and complications in the postoperative period [3].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of modern diagnosis methods associated to the improvement of the other methods that already exist has given rise to controversy regarding to the best way of diagnosing and tumor staging. Likewise, the role of surgery in palliation and technical aspects of the located injuries resection are far from reaching consensus on practice [3,4].…”
Section: Introductionmentioning
confidence: 99%